Juridical review of the transfer of property property that has not beenconverted into property rights - Sukma, Nina Fitria; Sulastri, Sulastri (UNIVERSITAS PAKUAN, 2025)
AbstractLand according to UUPA is the surface of the earth that can be given and owned by individuals or legal entities with state control over the land, water, and space for the welfare of the people. The UUPA requires property owners to convert rights within 20 years. Non-compliance with the conversion causes the land to become state property based on Permendagri Number 3 of 1979 and Government Regulation Number 18 of 2021. Normative juridical methods with legal and conceptual approaches as well as secondary data were used to analyze the legal consequences of the transfer of property rights that have not been converted. The results of the study show that the transfer of rights to eigendom verponding land that has not been converted into property rights is null and void because the object of the agreement is state land in accordance with Article 95 paragraph (1) of Government Regulation Number 18 of 2021 and does not receive legal protection due to the inconsistency between Government Regulation Number 24 of 1997 and Government Regulation Number 18 of 2021 which results in legal uncertainty for holders of eigendom verponding land rights who have not yet converting into property. The consequence is the loss of personal rights and material losses so that the public is advised to verify the status of the land before the transaction. Keyword: Eigendom Verponding, UUPA, Transfer of rights, Void by Law.